1993
DOI: 10.1071/ea9930373
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity to transplanted lettuce (Lactuca sativa) of three pre-emergence herbicides: metolachlor, pendimethalin, and propachlor

Abstract: The phytotoxicity of the pre-emergence herbicides metolachlor, pendimethalin, and propachlor to heading lettuce was investigated in 5 experiments conducted in southern Queensland during 1990-91. Metolachlor was applied before transplanting lettuce seedlings in 2 experiments. On a krasnozem soil at Toowoomba, spraying >1.75 kg a.i./ha reduced lettuce growth and the number of marketable lettuce heads. When applied on a black earth at Gatton, 1.44 kg a.i./ha stunted the lettuce and reduced the number of market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Results here are in agreement with Henderson and Webber (1993), who observed high tolerance of transplanted lettuce to pendimethalin (PRE) applied at rates between 0.5 and 2.6 kg ha À1 . In contrast, these authors observed lettuce injury and yield reduction caused by metolachlor (PRE) at rates higher than 1.4 kg ha À1 , whereas in our study, Figure 1.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Results here are in agreement with Henderson and Webber (1993), who observed high tolerance of transplanted lettuce to pendimethalin (PRE) applied at rates between 0.5 and 2.6 kg ha À1 . In contrast, these authors observed lettuce injury and yield reduction caused by metolachlor (PRE) at rates higher than 1.4 kg ha À1 , whereas in our study, Figure 1.…”
Section: Resultssupporting
confidence: 92%
“…S-metolachlor at 2.8 kg ha À1 was safe for the transplanted lettuce plants (Figures 1 and 2). The original metolachlor formulation (blend of isomers) used in the Henderson and Webber (1993) study vs. the purified S-metolachlor formulation used in this study might be the explanation for the differences in rates causing spinach injury (O'Connell et al 1998). However, PRE applications of S-metolachlor at the label rates recommended for other vegetables (0.7 to 1.1 kg ha À1 ) did not cause significant injuries and yield reduction, which indicate a possible role for this herbicide in transplanted lettuce.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…It was found that, dinitroaniline herbicides kill seedling weeds by inhibiting the development of lateral roots in susceptible plants, stunting the above-ground parts, with the development of a dark green color, swelling and brittleness of the stem or seedling hypocotyl (Parka and Soper, 1977). Severe crop phytotoxicity and damage symptoms reported in literature range from reduced or inhibited germination, reduced root length, protein and nucleic acid contents of root tips, injured flowers, to complete crop failure and residual persistence of herbicides in crop and soil (Henderson and Webber, 1993;Sinah et al, 1996). Pendimethalin caused seedling mortality (Aluka, 1997), but does not prevent seedling emergence (Akobundu, 1987;Smith, 2004;Smith, 2006).…”
Section: Phytotoxicity Assessmentmentioning
confidence: 99%
“…The phytotoxicity of dimethanamid and acetochlor was low in sunflower when applied preplanting and lightly soil-incorporated (Popescu 1995). Metolachlor and propachlor applied before transplanting were damaging to lettuce, and pendimethalin severely stunted lettuce when applied after transplanting (Henderson & Webber 1993). In dandelion, pre-emergence trifluralin (also incorporated), aziprotryne, chloroxuron and methabenzthiazuron were well tolerated in a direct seeded crop, but pendimethalin reduced plant numbers (Mitchell & Abernethy 1994).…”
Section: Introductionmentioning
confidence: 99%